Uplink resource allocation algorithms for Single-Carrier FDMA systems - Sokmen, Fatma Irem; Girici, Tolga (2010 European Wireless Conference, 2010)
We have focused on SC-FDMA based resource allocation in uplink cellular systems. Subchannel and power allocation constraints specific to SC-FDMA are considered. We considered a binary integer programming-based solution recently proposed for weighted sum rate maximization and extended it to different problems. We considered problems such as rate constraint satisfaction with minimum number subchannels and sum-power minimization subject to rate constraints. Besides stating the binary integer programming formulations for these problems, we propose simpler greedy algorithms for the three problems. Numerical evaluations show that the greedy algorithms perform very close to the optimal solution, with much less computation time.